Flowmetering for microfluidics. Issue 19 (30th June 2022) - Cavaniol, C.; Cesar, W.; Descroix, S.; Viovy, J.-L.
Abstract : This review critically analyzes the variety of methods to measure microfluidic flow rates as well as the development of metrological infrastructures for this purpose. Abstract : Originally designed for chromatography, electrophoresis, and printing technologies, microfluidics has since found applications in a variety of domains such as engineering, chemistry, environmental, and life sciences. The fundamental reason for this expansion has been the development of miniature components, allowing the handling of liquids at the microscale. For the maturation of microfluidic technologies, the need for affordable, reliable, and quantitative techniques to measure flow rates from 1 nL min −1 to 1 mL min −1 appears as a strong challenge. We review herein the different technologies available and those under development, and discuss their sensing principles and industrial maturity. Given the need of traceability of these measurements, we then focus on the developments of primary standards to measure microfluidic flow rates by metrological institutes. We conclude this review with some perspectives and pending challenges for microfluidic flowmeters.